Enhanced photoelectrochemical performance of 2D core-shell WO3/CuWO4 uniform heterojunction via in situ synthesis and modification of Co-Pi co-catalyst. (24th June 2020) - Hao, Zhichao; Liu, Zhifeng; Li, Yanting; Ruan, Mengnan; Guo, Zhengang
Abstract: In order to enhance the photoelectrochemical (PEC) performance of tungsten oxide (WO3 ), it is critical to overcome the problems of narrow visible light absorption range and low carrier separation efficiency. In this work, we firstly prepared the 2D plate-like WO3 /CuWO4 uniform core-shell heterojunction through in-situ synthesis method. After modification with the amorphous Co-Pi co-catalyst, the ternary uniform core-shell structure photoanode achieved a photocurrent of 1.4 mA/cm 2 at 1.23 V vs. RHE, which was about 6.67 and 1.75 times higher than that of pristine WO3 and 2D uniform core-shell heterojunction, respectively. Furthermore, the onset potential of 2D WO3 /CuWO4 /Co-Pi core-shell heterojunction occurred a negatively shifts of about 20 mV. Experiments illuminated that the enhanced PEC performance of WO3 /CuWO4 /Co-Pi photoanode was attributed to the broader light absorption, reduced carrier transfer barrier and increased carrier separation efficiency. The work provides a strategy of maximizing the advantages of core-shell heterojunction and co-catalyst to achieve effective PEC performance. Graphical abstract: Image 1 Highlights: WO3/CuWO4 uniform core-shell synthesis 2D heterojunction was prepared by in-situ method. CuWO4 nano-shell layer acts as light absorber to enhance absorption of visible light. 2D core-shell heterojunction accelerate charge separation and transfer. Co-Pi co-catalyst transfers holes to electrolyte to further enhance the carrier separation. WO3 /CuWO4 /Co-Pi photoanode shows more excellent performance in PEC water splitting.